2005
DOI: 10.1016/j.micres.2005.02.011
|View full text |Cite
|
Sign up to set email alerts
|

High temperature-induced changes in exopolysaccharides, lipopolysaccharides and protein profile of heat-resistant mutants of Rhizobium sp. (Cajanus)

Abstract: A thermosensitive wild-type strain (PP201) of Rhizobium sp. (Cajanus) and its 14 heat-resistant mutants were characterized biochemically with regard to their cell surface (exopolysaccharides (EPSs) and lipopolysaccharides (LPSs)) properties and protein profile. Differences were observed between the parent strain and the mutants in all these parameters under high temperature conditions. At normal temperature (30 degrees C), only half of the mutant strains produced higher amounts of EPSs than the parent strain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
1
21
0
3
Order By: Relevance
“…ATCC 33047 decreased with decrease in its optimal growth temperature from 40-45 to 30-35°C. Nandal et al (2005) reported high temperature On day zero, absorbance of the culture was set at A 660 , 0.1. In control cultures, medium contained 1.5 mM CaCl 2, 10 mM NO À 3 and no sodium chloride Data in the columns marked with similar lower case alphabets are not significantly different from one another at P \ 0.05 induced changes in exopolysaccharides, lipopolysaccharides and protein profile of heat-resistant mutants of Rhizobium sp.…”
Section: Kinetics Of Eps Productionmentioning
confidence: 99%
“…ATCC 33047 decreased with decrease in its optimal growth temperature from 40-45 to 30-35°C. Nandal et al (2005) reported high temperature On day zero, absorbance of the culture was set at A 660 , 0.1. In control cultures, medium contained 1.5 mM CaCl 2, 10 mM NO À 3 and no sodium chloride Data in the columns marked with similar lower case alphabets are not significantly different from one another at P \ 0.05 induced changes in exopolysaccharides, lipopolysaccharides and protein profile of heat-resistant mutants of Rhizobium sp.…”
Section: Kinetics Of Eps Productionmentioning
confidence: 99%
“…The ionizable functional groups of EPS such as carboxyl, phosphoric, amine, and hydroxyl groups aid in metal chelation. Different types of microorganisms have previously been studied in terms of their ability to produce EPS [14][15][16][17][18]. In these studies, EPS formation was strictly affected by environmental conditions such as heavy metal concentration, salt ions, pH level, temperature, oxygen concentration, or medium composition.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been reported for Azotobacter vinelandii grown on sucrose (Vermani et al, 1995) and for other EPS producting bacteria (Duta et al, 2004(Duta et al, , 2006. Although some studies have indicated that environmental conditions do not affect EPS biosynthesis (Jarman et al, 1978), others had opposite results (Nandal et al, 2005;Duta et al, 2006). pH and agitation have been described as the most influential factors on EPS yields (Vermani et al, 1995).…”
mentioning
confidence: 99%